2009
DOI: 10.1111/j.1460-9568.2009.06983.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of paraoxonase 1 genetic variants in Alzheimer’s disease neuropathology

Abstract: Evidence suggests that the genes involved in brain lipid homeostasis are of particular relevance for Alzheimer's disease (AD) etiology. Among these genes, that encoding paraoxonase 1 (PON1) has gained newfound interest from a public health perspective, as recent studies have suggested that PON1 L55M and Q192R genetic variants might affect individual susceptibility to environmental events, such as exposure to cholinesterase inhibitors. Cholinesterase inhibitor therapy being the treatment of choice for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…It was shown that low enzyme activity was associated with the increased oxidative stress, increased risk of cardiovascular disease, stroke and type 2 diabetes [2,17,23], known dementia risk factors [8]. Recently in autopsy-confirmed AD study of Leduc et al [21], PON1 p. L55M and p.Q192R genetic variants were significantly associated with β-amyloid levels, senile plaque accumulation and choline acetyltransferase activity in different brain areas. These observations could suggest an involvement of the PON1 in AD pathogenesis and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that low enzyme activity was associated with the increased oxidative stress, increased risk of cardiovascular disease, stroke and type 2 diabetes [2,17,23], known dementia risk factors [8]. Recently in autopsy-confirmed AD study of Leduc et al [21], PON1 p. L55M and p.Q192R genetic variants were significantly associated with β-amyloid levels, senile plaque accumulation and choline acetyltransferase activity in different brain areas. These observations could suggest an involvement of the PON1 in AD pathogenesis and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The carriers of R allele were found to be better responders [27]. This influence of the polymorphism could result from the interaction between PON1 and cholinesterase [4,21].…”
Section: Introductionmentioning
confidence: 95%
“…The association of PON1 gene polymorphism and risk of certain diseases has been documented (Sidoti et al, 2007;Leduc and Poirier, 2008;Agrawal et al, 2009;Leduc et al, 2009). In addition, PON1 gene polymorphisms (Q192R, L55M) alter both the level and activity of the enzyme (Humbert et al, 1993;Garin et al, 1997;Mackness et al, 1998;Aviram et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who developed dementia were found to have a higher frequency of the 55M allele (91)(92). Although Helpecque et al reported that the -107T allele meant high risk of dementia (93), it was concluded in another study that this observation was a contradiction (94).…”
Section: Clinical Significancementioning
confidence: 75%